1996
DOI: 10.1152/jn.1996.75.4.1673
|View full text |Cite
|
Sign up to set email alerts
|

Hunger and satiety modify the responses of olfactory and visual neurons in the primate orbitofrontal cortex

Abstract: SUMMARYAND CONCLUSIONS1. The primate orbitofiontal cortex is the site of convergence of information from primary taste and primary olfactory cortical regions. In addition, it receives projections from temporal lobe visual areas concerned with the representation of objects such as foods. Previous work has shown that the responses of gustatory neurons in the secondary taste area within the orbitofrontal cortex are modulated by hunger and satiety, in that they stop responding to the taste of a food on which an an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
290
2
6

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 432 publications
(328 citation statements)
references
References 39 publications
30
290
2
6
Order By: Relevance
“…The model's response to devaluation, in the CS-FSS (foodspecific satiety) and US-FSS tasks, replicates reported behavioral patterns and electrophysiological neural responses (Rolls et al, 1986;Scott et al, 1995;Critchley and Rolls, 1996;Rolls et al, 1999). Experiments that assay behavioral responses to increasing satiety reveal that animals quickly switch from acceptance to rejection of food rewards such as juice.…”
Section: Influence Of Satiety On Valuesupporting
confidence: 65%
See 2 more Smart Citations
“…The model's response to devaluation, in the CS-FSS (foodspecific satiety) and US-FSS tasks, replicates reported behavioral patterns and electrophysiological neural responses (Rolls et al, 1986;Scott et al, 1995;Critchley and Rolls, 1996;Rolls et al, 1999). Experiments that assay behavioral responses to increasing satiety reveal that animals quickly switch from acceptance to rejection of food rewards such as juice.…”
Section: Influence Of Satiety On Valuesupporting
confidence: 65%
“…Experiments that assay behavioral responses to increasing satiety reveal that animals quickly switch from acceptance to rejection of food rewards such as juice. In particular, experiments that assay neuronal responses during trials where juice is consumed with increasing satiety have found that neurons have a logistically decreasing response to US or CS presentation as satiety increases (Rolls et al, 1986;Critchley and Rolls, 1996). The model exhibits the FSS property in that both simulated and electrophysiologically recorded neurons in the AMYG, LH, ORB have diminished responses to a sated food, but preserved responses to an unsated food (Rolls et al, 1986;Nishijo et al, 1988a).…”
Section: Influence Of Satiety On Valuementioning
confidence: 99%
See 1 more Smart Citation
“…Sensory-specific satiety can be defined as the implicit memory for consumed food items, characterized by a decrease in pleasure derived from recently consumed food items while other unconsumed food items are still pleasurable. Sensory-specific satiety is mediated by the orbitofrontal cortex [25] and not by the hippocampus.…”
Section: Hippocampus and Memory For Food Intakementioning
confidence: 95%
“…However, an imaging study in a control group of nonobese individuals, 12 together with research from other groups, [13][14][15] has shown that the motivation to eat is controlled by an extensive system of reciprocally connected neural areas, beyond the hypothalamus, mediating both the intrinsically derived hunger drive to eat and the extrinsically derived incentive to eat. 12,16 Key brain regions for the former include the hypothalamus 11,[17][18][19] striatum, 20 orbitofrontal cortex (OFC) [21][22][23] insula [24][25][26] and anterior cingulate cortex, 24 and, for the latter, the amygdala and OFC. [27][28][29][30] Indeed, Lucignani et al 31 have found altered cerebral GABA A receptor function in the insula and cingulate, frontal and temporal neocortices in six adults with PWS compared to controls.…”
Section: Introductionmentioning
confidence: 99%